Strategi Guru Ngaji dalam Meningkatkan Kemampuan Membaca Al-Qur’an Santri di TPQ Babul Falah - Fajri, Aulia; Ikhlas, Al (Darul Yasin Al Sys, 2023)
This research aims to determine the strategies used by teachers to improve students' Al-Quran reading skills. This type of research is qualitative. The informants for this research were teachers and students. Data collection techniques using observation, interviews and documentation. Based on the data analysis, it was concluded that the teacher's strategy in improving students' Al-Quran reading skills was that the teacher prepared it by preparing a plan in the form of determining the goals to be achieved, choosing an approach, choosing a method and determining indicators of success so that the steps taken by the teacher were clear and in line with the expected goals. Factors that support teachers' strategies in improving students' Al-Quran reading skills are sincere intentions within the Koran teacher, students having the ability to read the Koran, a supportive family environment, competent Koran teachers who can explain in easy-to-understand language, and the students' willingness to Study. Meanwhile, the inhibiting factors are the lack of adequate facilities and infrastructure as well as the lack of motivation and interest from students to study the Koran. To overcome these obstacles, teachers always provide motivation to students and work together with parents.